2006
DOI: 10.1158/0008-5472.can-06-2473
|View full text |Cite
|
Sign up to set email alerts
|

Mammary-Specific Ron Receptor Overexpression Induces Highly Metastatic Mammary Tumors Associated with β-Catenin Activation

Abstract: Activated growth factor receptor tyrosine kinases (RTK) play pivotal roles in a variety of human cancers, including breast cancer. Ron, a member of the Met RTK proto-oncogene family, is overexpressed or constitutively active in 50% of human breast cancers. To define the significance of Ron overexpression and activation in vivo, we generated transgenic mice that overexpress a wild-type or constitutively active Ron receptor in the mammary epithelium. In these animals, Ron expression is significantly elevated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
151
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(160 citation statements)
references
References 42 publications
9
151
0
Order By: Relevance
“…Elevated RON expression was strongly correlated to phosphorylation and invasive activity of tumors (12), thus suggesting that increased RON expression plays a role in the progression of carcinomas to invasive-metastatic phenotypes. Mammary-specific RON receptor overexpression induced metastatic mammary tumors that has been shown to involve ␤-catenin activation (24). Our data clearly demonstrated that MSP stimulates the invasive phenotype of MDA MB 231 and MDA MB 468 breast cancer cells (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…Elevated RON expression was strongly correlated to phosphorylation and invasive activity of tumors (12), thus suggesting that increased RON expression plays a role in the progression of carcinomas to invasive-metastatic phenotypes. Mammary-specific RON receptor overexpression induced metastatic mammary tumors that has been shown to involve ␤-catenin activation (24). Our data clearly demonstrated that MSP stimulates the invasive phenotype of MDA MB 231 and MDA MB 468 breast cancer cells (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…Transgenic overexpression of Ron in MMTV-Ron mice is sufficient to induce mammary tumors that metastasize to the liver and lungs with high penetrance. In contrast to the MET RTK, activating mutations in Ron did not confer a higher tumor incidence or metastasis rate [92].…”
Section: Conventional Transgenics: Receptor Tyrosine Kinasesmentioning
confidence: 91%
“…RON is composed of a 45 kDa extracellular ·-chain and a 150 kDa transmembrane ß-chain linked by a disulphide bond (7). Recent studies have uncovered a previously unrecognized link between aberrant RON expression and pathogenesis of human epithelial cancers including those from breast and colon (8)(9)(10)(11). Immunohistochemical staining of primary cancer samples has revealed that RON is overexpressed at around 50% of primary breast cancer sampled with different histological subtypes (8,12).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression associates with the diseases at any stage, correlates with the post-menopausal status (8), and serves as an independent predictor of distant relapse in breast cancer patients (13). Biochemically, RON overexpression causes constitutive tyrosine phosphorylation, which stimulates downstream signaling pathways including MAP kinase and PI-3 kinase (8)(9)(10)(11). These activities lead to dramatic cellular morphological changes with increased cell migration and matrix invasion (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation